Influence of Prostate Stem Cell Antigen Gene Polymorphisms on Susceptibility to Helicobacter pylori‐associated Diseases: A Case‐control Study. Issue 2 (12th January 2015) - Ichikawa, Hitomi; Sugimoto, Mitsushige; Uotani, Takahiro; Sahara, Shu; Yamade, Mihoko; Iwaizumi, Moriya; Yamada, Takanori; Osawa, Satoshi; Sugimoto, Ken; Miyajima, Hiroaki; Yamaoka, Yoshio; Furuta, Takahisa
<x xml:space="preserve">Abstract</x> Background Patients with duodenal ulcer have a reduced risk of developing gastric cancer compared to those without. Recently, the prostate stem cell antigen (PSCA) rs2294008 C>T polymorphism was found to be associated with different pathogenesis of duodenal ulcer and gastric cancer developments. However, whether PSCA rs2294008 C>T polymorphism is associated with severity of gastric mucosal atrophy is unclear. We examined the influence of the PSCA rs2294008 C>T polymorphism on susceptibility to H. pylori‐related diseases and the relationships between PSCA polymorphism and gastric mucosal atrophy. Methods PSCA rs2294008 C>T polymorphism was assessed in H. pylori‐positive Japanese patients (n = 488) with noncardia gastric cancer (n = 193), gastric ulcer (n = 84), duodenal ulcer (n = 61), and atrophic gastritis (n = 150), as well as in H. pylori‐negatives (n = 266). Results Frequency of PSCA rs2294008 C/C genotype in duodenal ulcer was 36.1%, which was significantly higher than those with gastric cancer (12.4%), gastric ulcer (19.0%), gastritis (10.7%), and H. pylori‐negatives (19.5%) (p < .001). Compared with duodenal ulcer, having the T allele significantly increased the risk of gastric cancer (OR: 3.97, 95% CI: 2.02–7.80; p < .001), gastric ulcer (2.40, 1.13–5.10; p = .023), and gastritis (4.72, 2.26–9.86; p < .001). Mean pepsinogen (PG) I/PG II ratio in T allele carriers (2.17 ± 0.75) was significantly lower than that in C/C genotype (3.39 ± 1.27, p < .001). Conclusions The PSCA rs2294008 C>T polymorphism is associated with differing susceptibilities to H. pylori‐associated diseases. The PSCA rs2294008 C>T polymorphism may be acting through induction of gastric mucosal atrophy, finally leading to development of gastric ulcer and gastric cancer in PSCA rs2294008 T allele carriers, but not duodenal ulcer.